2005
DOI: 10.1080/13921657.2005.10512702
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Different Cadmium Concentrations on Survival Reproduction and Adaptation ofEisenia Fetida Californica

Abstract: The article deals with the effects of different Cd concentrations (5 and 50 mg kg -1 ) in municipal sewage sludge compost on survival, activity and adaptation of Eisenia fetida californica earthworms. Investigations were carried out under laboratory conditions. Experiments were also conducted on adaptation of second-generation juveniles to Cd-contaminated sludge substrates. Dynamics of Cd concentrations in sludge, earthworm tissues and compost-grown lettuce was constantly monitored. Cd concentrations in earthw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
1
0
0
Order By: Relevance
“…The worms living in metal polluted soils reached the lower weight or needed more time to reach the maximum weight than in non-polluted sites (Spurgeon and Hopkin, 1996). Heavy metal concentration in the substrate significantly reduced the growth of E. fetida (Matuseviciute et al, 2005). The results of the present study are in agreement with the work of Zaltauskaite (2010) who reported that E. fetida exposed to different concentrations of lead in soil tended to lose more weight than those in control.…”
Section: Changes In Body Weightsupporting
confidence: 90%
“…The worms living in metal polluted soils reached the lower weight or needed more time to reach the maximum weight than in non-polluted sites (Spurgeon and Hopkin, 1996). Heavy metal concentration in the substrate significantly reduced the growth of E. fetida (Matuseviciute et al, 2005). The results of the present study are in agreement with the work of Zaltauskaite (2010) who reported that E. fetida exposed to different concentrations of lead in soil tended to lose more weight than those in control.…”
Section: Changes In Body Weightsupporting
confidence: 90%